Inactivation of LEF1 in T-cell acute lymphoblastic leukemia - Gutierrez, Alejandro (American Society of Hematology, 2010)
To further unravel the molecular pathogenesis of T-cell acute lymphoblastic leukemia (T-ALL), we performed high-resolution array comparative genomic hybridization on diagnostic specimens from 47 children with T-ALL and identified monoallelic or biallelic LEF1 microdeletions in 11% (5 of 47) of these primary samples. An additional 7% (3 of 44) of the cases harbored nonsynonymous sequence alterations of LEF1, 2 of which produced premature stop codons. Gene expression microarrays showed increased expression of MYC and MYC targets in cases with LEF1 inactivation, as well as differentiation arrest at an early cortical stage of thymocyte development characterized by expression of CD1B, CD1E, and CD8, with absent CD34 expression. LEF1 inactivation was associated with a younger age at the time of T-ALL diagnosis, as well as activating NOTCH1 mutations, biallelic INK4a/ARF deletions, and PTEN loss-of-function mutations or activating mutations of PI3K or AKT genes. These cases generally lacked overexpression of the TAL1, HOX11, HOX11L2, or the HOXA cluster genes, which have been used to define separate molecular pathways leading to T-ALL. Our findings suggest that LEF1 inactivation is an important step in the molecular pathogenesis of T-ALL in a subset of young children.